Nanostructured composite materials for solar energy conversion - Brennan, Lorcan J. (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
Sunlight is the largest of all available carbon neutral energy sources. Hence the development of solar energy devices, which can create energy from the sun are of extreme importance to society. In 1991, Gratzel et al. developed a new type of solar energy device, which could effectively convert solar radiation into electrical power. This device is known as the dye sensitized solar cell (DSSC). This development heralded a new era in solar energy research as scientists and engineers developed methods of increasing device efficiency, longevity and routes towards successful scale up of this technology. Largely speaking the DSSC has numerous advantages when compared to conventional Si based devices, which currently dominate the market. DSSCs are relatively easy to produce from cheap abundant materials and they can work effectively in various weather conditions (e.g. under diffuse light and indoors).
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin